MOTIVASI SURIAH MEREBUT KEMBALI DATARAN TINGGI GOLAN DARI ISRAEL TAHUN 2009 - Wanto, Dion Wahyudi; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research was conducted to explain what Motivated Syria retake the Golan Heightsfrom Israel . Political situation in the Middle East is an issue that is very interesting to studybecause of frequent konflik.Salah only is the conflict between Syria and Israel . The conflictbetween the two sovereign States of this stems from the Israeli occupation of the Golan Heightsin the Six-Day War in 1967 .In this research the authors obtain and collect data through research Librarianship (library research ) derived from the sources of literature ( books ) , magazines , newspapers ,articles from scientific journals and published - written publications that support data collectionto explain what motivated syria retake the Golan Heights from israel . The theory is that theauthors use Geopolitics Theory , supported by the concept of national interest .After the war , Israel seized the Golan Heights from Syria . Israel apply the law ofjurisdiction in the Golan Heights . The conquest of the Golan Heights to Syria is everything , it isbecause the condition of the Golan Heights region has a special topography . In addition to theeconomic potential and natural resources in the high plateau region of the Golan , Golan alsogives the value of defense and security for those who master it . Position which is located on theborder between the two countries have implications for the ability to control and anticipation inthe military field.KeyWords : Golan Heights, Conflict, Syiria-Israel, Position Strategic, Motivated, NationalInterest.